Advertisement Remove all ads

Solve: X4 – 2x² – 3 = 0. - Mathematics

Sum

Solve: x4 – 2x² – 3 = 0.

Advertisement Remove all ads

Solution

x4 – 2x² – 3 = 0

`=> x^4 - 3x^2 + x^2 - 3 = 0`

`=> x^2(x^2 - 3) + 1(x^2 - 3) = 0`

`=> (x^2 - 3)(x^2 + 1) =0`

If `x^2 - 3 = 0` or `x^2 + 1 = 0`

then `x^2 = 3` or `x^2 = -1` (reject)

`=> x = +- sqrt3`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 5 Quadratic Equations
Exercise 5 (E) | Q 7 | Page 66
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×